Assessment of economic viability and production costs for the innovative microfiltered digestate. (15th April 2023) - Pappalardo, Gioacchino; Trimarchi, Ettore; Selvaggi, Roberta
Abstract: This paper assesses the economic viability of the production process of an innovative form of digestate known as "microfiltered digestate", suitable for use as a fertilizer in driplines for permanent crops. A Break-Even Analysis was performed to determine the Break-Even Point which identifies the minimum quantity of products necessary to cover production costs at a certain selling price. Our results show that the production of microfiltered digestate provides positive economic viability for anaerobic digestion managers, providing them with an attractive market outlet and, at the same time, a new form of income. The experimental study was stated in Sicily, but it is replicable in any territorial context with anaerobic digestion plants. The results are in line with the principles of circular economy and are very current with reference to the use of organic fertilizers instead of chemical ones. Highlights: Innovative micro-filtered digestate (MFD) is a new source of income. A stategy to decrease the degree of dependence on public subsidies. Break-Even Analysis was made to determine lower convenient level of production. Break-Even Point was estimated for three different selling price. MFD guarantee high economic profitability for the companies that produce it.